Pharmacist Assistants' role in medicine supply management at a primary healthcare setting - Sibusiso M. Zuma (AOSIS, 2022)
Background: The need to improve essential medicine supply in the public sector is of paramount importance to ensure that the drugs used in treatment regimens are accessible, acceptable, safe, cost effective and affordable to the population. Aim: To assess the role of post-basic pharmacist assistants at primary healthcare clinics in order to make recommendations aimed at improving essential medicine supply management. Setting: The study covered five provinces namely: Eastern Cape, Free State, Gauteng, KwaZulu-Natal and Mpumalanga. Method: A qualitative, exploratory, descriptive research design was followed, using a semi-structured interview guide to collect data from 11 District Pharmaceutical Service Managers together with medicine availability reports review. Data analysis was performed using Colaizzi's steps. Results: The study found that there is a shortage of post-basic pharmacist assistants in primary healthcare clinics, which affects the management and availability of medicine supplies. Placement of the post-basic pharmacist assistants would improve medicine supply management in the primary healthcare clinics. Conclusion: At least one post-basic pharmacist assistant should be appointed at each primary healthcare clinic in order to ensure efficient medicine supply management and consistent medicine availability. Contribution: The study provides evidence that primary healthcare clinics without post-basic pharmacist assistants are more likely to have erratic medicine supply management practices and confirms that post-basic pharmacist assistants play a positive role in the medicine supply management processes in primary healthcare clinics.